Impact of Customer Relationship Management (CRM) on Organizational Performance: A Study from the Perspective of Bangladesh - Rahman, Md. Mostafijur; Hussain, Md. Tuhin; Moon, Shahnaz Parvin; Tisha, Monika Mehjabeen; Lima, Mumtahina Tahsin (American Journal of Trade and Policy, 2021)
Customer relationship management is recognizing, attracting, obtaining, maintaining, and keeping profitable and faithful customers as the success of a business highly depends on them. The current study’s purpose is to measure the impact of customer relationship management on organizational performance. The study used Yamane’s (1967) formula to calculate the sample, and it has got 90 sample sizes and used semi-structured questionnaires containing pre-coded and open-ended questions. Descriptive statistics like frequency, percentages, and means have been performed. Besides, inferential statistics like correlation and regression analysis have been used to determine the relationship. The result showed that customer relationship management significantly and positively impacts organizational performance. The study will help the policy maker of any organization to rethink and give much more emphasis to customer relationship management.
Keywords: Customer Relationship Management; Organizational Performance; Correlation; Management of Customer Knowledge; Customer Orientation